2021
DOI: 10.1111/ped.14602
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of pediatric coronavirus disease 2019 and predictors of polymerase chain reaction positivity

Abstract: Background To identify the clinical findings and outcomes of children with COVID‐19 and factors predicting RT‐PCR positivity. Methods The data retrospectively analyzed for suspected and confirmed pediatric COVID‐19 patients between March 20 and May 31, 2020. Results There were 404 children, of them, 176 (43.6%) patients were confirmed to have COVID‐19 which were less symptomatic on admission (67.6% to 95.6%). Cough (44.9%), fever (38.1%), sor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 40 publications
2
13
0
Order By: Relevance
“…Our clinical findings were compared with those observed in the other European cohorts of children presenting in the ED [ 13 20 ] as resulted by our scoping review (Table 2 ).Similar prevalence of symptoms was observed in all cohorts. Fever was always the main symptom (43%–82%) except for Turkish cohort in which a different definition of fever wad adopted (>38.0°C compared to >37.5°C for other studies).…”
Section: Resultssupporting
confidence: 59%
“…Our clinical findings were compared with those observed in the other European cohorts of children presenting in the ED [ 13 20 ] as resulted by our scoping review (Table 2 ).Similar prevalence of symptoms was observed in all cohorts. Fever was always the main symptom (43%–82%) except for Turkish cohort in which a different definition of fever wad adopted (>38.0°C compared to >37.5°C for other studies).…”
Section: Resultssupporting
confidence: 59%
“…A total of 18 studies reported prevalence of smell and/or taste dysfunction, most of them reported more than one type of prevalence among children with COVID-19. Specifically, 11 of the included studies reported the prevalence on smell dysfunction ( 13 , 25 , 27 , 28 , 30 , 34 36 , 40 ), 9 of the included studies reported prevalence on taste dysfunction ( 13 , 27 , 28 , 32 , 34 , 37 , 38 , 40 ), 10 of the included studies reported prevalence on smell or taste dysfunction ( 13 , 14 , 25 , 26 , 28 , 29 , 31 , 33 , 36 , 39 ), and 2 of the included studies reported prevalence on smell and taste dysfunction ( 13 , 28 ). Thus, four different types of prevalence were analyzed.…”
Section: Resultsmentioning
confidence: 99%
“…History of contact with an individual infected by COVID-19 was reported as a predictor for PCR positivity. 14 The lower percentage of susceptibility in the pediatric population could be explained by differences in symptomatic infection rates and subsequent issues with case ascertainment. 15 Household transmission studies found that pediatric cases were usually identified through contact tracing of adults, although some case reports documented transmission from children to adults.…”
Section: Discussionmentioning
confidence: 99%